2020
DOI: 10.1002/maco.201911347
|View full text |Cite
|
Sign up to set email alerts
|

An amino‐based protic ionic liquid as a corrosion inhibitor of mild steel in aqueous chloride solutions

Abstract: Protic ionic liquids (PILs) have shown to be promising substances as corrosion inhibitors (CIs). In line with this, the aim of this study is to study the performance and propose the corrosion inhibition mechanism of N-methyl-2hydroxyethylamine (M-2HEAOL) and bis-2-hidroxyethylamine (B-HEAOL) oleate, for mild steel, in a neutral chloride solution. Electrochemical characterization was conducted under static and hydrodynamic conditions, and it was revealed that M-2HEAOL and B-HEAOL worked as mixed-type CIs with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 87 publications
1
19
0
2
Order By: Relevance
“…This mitigated formation of iron oxide-hydroxide is caused by the blocking effect of the inhibitor, which is supported by polarization curves. In addition, as reported by Schmitzhaus et al, [36] the PIL is able to form complexes with iron. It may promote the growth of the PIL adsorbed layer, as found by other authors for different inhibitors.…”
Section: Raman Spectroscopysupporting
confidence: 64%
See 2 more Smart Citations
“…This mitigated formation of iron oxide-hydroxide is caused by the blocking effect of the inhibitor, which is supported by polarization curves. In addition, as reported by Schmitzhaus et al, [36] the PIL is able to form complexes with iron. It may promote the growth of the PIL adsorbed layer, as found by other authors for different inhibitors.…”
Section: Raman Spectroscopysupporting
confidence: 64%
“…The role of the double bond (unsaturation) in oleic part of PIL is believed to contribute to the efficiency, because the unsaturation can be adsorbed on the metal surface by a flat adsorption process, reducing the presence of active sites and blocking the corrosion process, as Schmitzhaus et al [36] observed using the same IL in a nearly neutral solution. Porcayo-Calderon et al [94] also reported the contribution of unsaturation in the alky chains of inhibitors to the efficiency in corrosion inhibition.…”
Section: Inhibition Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…A Figura 1a apresenta os espectros de FTIR obtidos para a monoetanolamina, o ácido acético e o líquido iônico 2-HEAA. Os espectros característicos dos precursores da síntese são bem conhecidos e já foram descritos na literatura (BARBOSA, 2013;SCHMITZHAUS et al, 2020;CAMARGO et al, 2016 (ALVAREZ et al, 2011;BARBOSA, 2013;SCHMITZHAUS et al, 2020;CAMARGO et al, 2016…”
Section: Caracterização Do Acetato De 2-hidroxietilamônio (2-heaa)unclassified
“…-H, que sobrepõem as bandas de estiramento de N-H da monoetanolamina e do cátion do LIP(ALVAREZ et al, 2011;BARBOSA, 2013;SCHMITZHAUS et al, 2020;CAMARGO et al, 2016).…”
unclassified